Protective effect of physical activity on small airway function across different age groups - Shelat, Foram; Jasani, Kena (International Journal of Research in Medical Sciences, 2026)
Background: Small airways play a critical role in maintaining efficient pulmonary function and are often the earliest site of age-related and inactivity-related functional decline. Regular physical activity is known to improve respiratory mechanics, but its protective effect on small airway function across age groups remains unclear. The aim of the study was to evaluate the impact of physical activity and aging on small airway function in adults using expiratory flow rate parameters. Methods: A cross-sectional study was conducted among 1000 participants in Anand and Kheda Districts. Participants were categorized into four groups (n=250 each): young exercisers (YE), young non-exercisers (YNE), elderly exercisers, and elderly non-exercisers. Spirometric assessment was performed to measure small airway parameters, including MEF25, MEF50, MEF75 and MEF25-75, and peak expiratory flow (PEF). Comparisons were made to assess the effects of age and exercise on small airway function. Results: Exercisers in both the young and elderly groups demonstrated higher mean expiratory flow rates across all MEF parameters than non-exercisers. YE demonstrated the highest pulmonary efficiency, with a PEF of 10.2±0.8 suggesting an improved overall airflow capacity. Small airway function, measured via MEF 25-75, was highest in the YE group (4.5±0.4) and lowest in the elderly non-exercisers (ENE) group (3.5±0.3) (p<0.05). Elderly non-exercisers showed the lowest values, indicating a pronounced decline in small airway function with aging and inactivity. Conclusions: The study highlights the protective role of regular physical activity in preserving small airway function across different age groups. Although aging is associated with a decline in expiratory flow rates, regular exercise significantly attenuates this decline. Promoting physical activity may therefore be an effective strategy for maintaining respiratory health and preventing early small airway dysfunction.